95.1k views
2 votes
x(x+3)(x+3)=0 Please I NEED HELP FAST! PLLLLLLLLLLLLLLLLLLLLLLLLLLEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEAAAAAAAAAAAAAAAAAAAAAAAAAAAAASSSSSSSSSSSSSSSSSSSSSSSSSSEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEEE!

2 Answers

5 votes


\text{If } \: a\cdot b \cdot c = 0 \text{ then } a=0 \text{ or } b =0 \text{ or } c=0 \text{ or all of them are equal to zero.}


x(x+3)(x+3) =0


\boxed{x_1 =0}


x_2+3 =0


\boxed{x_2 = -3}


x_3+3 =0


\boxed{x_3 = -3}

User Roderick
by
5.0k points
5 votes

Answer:


\boxed{x^3+6x^2+9x}

Explanation:


x(x+3)(x+3)

Resolving the first parenthesis


(x^2+3x) (x+3)

Using FOIL


x^3+3x^2+3x^2+9x

Adding like terms


x^3+6x^2+9x

User FURKAN ILGIN
by
4.8k points